PENGARUH ORGANISATION CITIZENSHIP BEHAVIOR, PERILAKU INOVATIF, DAN LOYALITAS TERHADAP KINERJA KARYAWAN - Sigit Riyanto; Sutrisno; Qristin Violinda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The purpose of this research is to analyze the influence of Organizational Citizenship Behavior, Innovation Behavior, and Loyalty on Employee Performance at PT Talindo. The advantage of this research is that it can be used as input for preparing and determining appropriate human resource management strategies to achieve results that further optimize employee performance in an organization. The research population consisted of all 86 PT Tarindo employees, and non-probability sampling techniques were used to take a sample of 86 PT Tarindo respondents. Saturation sampling (census). Analysis of this research data uses multiple regression analysis of the SPSS version 24 program, and the results of the analysis and discussion show that Organizational Citizenship Behavior has a partially positive and significant effect on employee performance; Innovative behavior is proven to have a positive and significant influence. . Employee performance and loyalty have a positive and significant influence on the performance of PT Tarindo employees